Media Use, Political Participation and the Level of Digitization. A Comparative Analysis of EU Countries - Splendore, Sergio (PARTECIPAZIONE E CONFLITTO, 2016)
The paper analyses six rounds of the European Social Surveys (from 2000 to 2012) to explore how 1) media uses, 2) unconventional and 3) conventional (i.e. voting) forms of political participation have changed in sixteen European countries. Additionally, the research considers one of the latest surveys to investigate the relation between media use and participation in the contemporary period characterized by open data and e-government. The level of digitization in each country is assessed according to its infrastructure, the legal framework (namely the Freedom of Information Act), the quality of the data available from the public administration, and e-government development in terms of online services. The research question is whether use of the Internet and the level of national digitization affect unconventional forms of political participation. The results demonstrate that both the country’s level of digitization at the macro level and the use of the Web at the individual level are co-determinants of the forms of political participation considered. However, the level of digitization does not affect voting.